Voices of the crisis, faces of unemployment - Rodríguez, Raúl; Rico, Andrea (Razón y fe, 2018)
In this article, we offer an approach to the reality of the current economic crisis, as experienced by the people directly affected by it. It is, therefore, a complementary article to others that appear in this same issue of Razón y Fe: the editorial comment of the editorial board, the contribution of the General Secretary of Caritas Española and the proposals of economist José Ramón de Espínola. Here, we offer the pages of our magazine to those who suffer from the crisis, but can hardly speak out. There are five interviews that bring us closer to five voices of the crisis, five faces of unemployment.